1993
DOI: 10.1002/j.1556-6676.1993.tb02661.x
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental Behaviors Following Test Administration and Interpretation: Exploration Validity of the Strong Interest Inventory

Abstract: A two‐phase longitudinal study was conducted to explore the exploration validity (i.e., the power of interest inventories to facilitate career exploration activities such as talking to professionals and seeking vocational information) of the 1985 Strong Interest Inventory (SII) for college students. Participants in the study included an experimental group (N =75), which participated in the SII testing and a group interpretation, and a contrast group(N=67). Students in the experimental group reported significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…Previous research has shown that students who completed and received interest inventory feedback had higher levels of career decision self-efficacy than did a control group who did not receive feedback (Luzzo & Day, 1999). The process of providing feedback about interests has also been shown to increase exploration behaviors (Randahl, Hansen, & Haverkamp, 1993), which appeared to be important for career decision self-efficacy in the current study. Thus, assessing and discussing clients' interest profiles with them may facilitate career decision making directly or indirectly and may be especially useful for those with lower identity status characteristics because they are likely to have lower career decision self-efficacy.…”
Section: Discussionmentioning
confidence: 70%
“…Previous research has shown that students who completed and received interest inventory feedback had higher levels of career decision self-efficacy than did a control group who did not receive feedback (Luzzo & Day, 1999). The process of providing feedback about interests has also been shown to increase exploration behaviors (Randahl, Hansen, & Haverkamp, 1993), which appeared to be important for career decision self-efficacy in the current study. Thus, assessing and discussing clients' interest profiles with them may facilitate career decision making directly or indirectly and may be especially useful for those with lower identity status characteristics because they are likely to have lower career decision self-efficacy.…”
Section: Discussionmentioning
confidence: 70%
“…Despite issues with inventories, those who have interest inventories interpreted for them participate in more career exploration than those who do not (Randahl, Hansen, & Haverkamp, 1993). Despite its limitations, data from the O*NET-IP-SF can still be utilized to guide hypothesis formation (Hansen, 2013), to begin a narrative of manifest interests (Savickas, 2015), and to assess saliency of one’s cultural background and individual differences (Fouad & Kantamneni, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A number of career-specific domains have also been found to be significantly improved by career counseling, with particularly robust improvements in “career certainty decidedness” and “career maturity.” Both of the meta-analyses indicate that individual career counseling is more effective than either group counseling or computer-based interventions. More specifically, career counseling techniques that utilize interest interventions have been found to increase career exploration (Randahl, Hansen, & Haverkamp, 1993) and reduce vocational decision-making difficulties (Di Fabio & Gideon, 2013).…”
Section: Interests In Career Assessment and Counselingmentioning
confidence: 99%